Study on structure of the Earth’s crust in Thua Thien-Hue province and adjacent areas by using gravity and magnetic data in combination - Hung, Pham Nam; Trong, Cao Dinh; Dung, Le Van; Tuan, Thai Anh; Bach, Mai Xuan; Duong, Nguyen Anh (Vietnam Journal of Marine Science and Technology, 2020)
This paper presents the structural characteristics of the Earth’s crust in Thua Thien-Hue province and adjacent area based on interpretation of gravity and magnetic data in combination. Research results have shown that: The depth of crystalline basement varies complicatedly, in the range of 0–11 km. The depth of Conrad surface increases from Northeast (12 km) to Southwest (18 km) and the depth of Moho surface is 23–34 km; The density of sedimentary layer changes from 2.61 g/cm3 to 2.65 g/cm3. Meanwhile, the density of granitic layer is in the range of 2.68–2.73 g/cm3. The basaltic layer has the density value of 2.88–2.93 g/cm3 and the average density of lower layer of the Earth’s crust is about 3.30 g/cm3; The depth of second-order faults, Red River and A Luoi - Rao Quan, is through the Earth’s crust. Meanwhile, the depth of influence of third-order faults, Chay river, Dong Ha - Phu Vang, Vinh Linh, Hue - Son Tra and Tam Ky - Phuoc Son, is within the thickness of the Earth’s crust.